IMAGING TROPICAL PEATLAND AND AQUIFER POTENTIAL IN SOUTH SUMATERA USING ELECTRICAL RESISTIVITY TOMOGRAPHY - Muhammad Rizki Ramdhani; Acep Ruhimat; Wiyono Wiyono; Ahmad Barnes (Indonesian Journal of Forestry Research, 2020)
Indonesia has one of the largest tropical peatland areas in the world. In Sumatra Island, peatland is spread over 11 areas and it was mainly found in Riau (60.1%) and South Sumatra (19.6 %) Provinces. This study investigates the subsurface of tropical peatland in Ogan Komering Ilir Regency, South Sumatra Province. Data was recorded using Electrical Resistivity  Tomography (ERT) method based on the sub-surface images of tropical peatland. This study was conducted based on dipole-dipole configuration with 72 channels spread. This paper also studies the physical properties (thickness and electrical resistivity) of peatland and its substrate using ERT. In this study the ERT section and the geological map identified Alluvium (Qs), Kasai Formation, and the Basement. Result shows the ERT is applicable for imaging the thickness of tropical peatland and other geological features (Aquifer, geological structures, and stratigraphy). The electrical resistivity of peat varies from 20 ohm meter to 120 ohm meter and the thickness of peat varies from 2–5 meter. In some ERT sections, the basement was identified from 130 meter to 170 meter beneath the surface. The aquifer sweet spots were located from ERT Sections combined with the hydrogeological map. The aquifer was identified in Kasai Formation. The thickness of the aquifer layer is 2–20 meter. These physical properties may support the peatland conservation (forest fire mitigation) and geotechnical analysis purposes.